Inês de Castro in Scenic and Performative Visions: Studies on the Digital Collection of the Museu Nacional do Teatro e da Dança of Portugal - Augusto, Michele (Mimesis Journal, 2024)
The article presents an analysis of the sensitive journey in the Museu do Teatro e da Dança National (MNTD) of Portugal, digital collection content. The visions of Inês de Castro, the costume design creations by various artists in productions by Portuguese theatrical companies between the 1940s and 1970s. The concepts and visuality of the story and characters are transported through the traces of the costumes designed of various Portuguese Companies, photographs and drawings composing a collection of memories able to feed new creations. The intention is to present memories and show how they can be used for new costume designs.